Preferences toward the constructivist smart classroom learning environment: examining pre-service teachers' connectedness. Issue 3 (3rd April 2019) - Li, Yanhong; Yang, Harrison Hao; MacLeod, Jason
ABSTRACT: The constructivist smart classroom learning environment is quickly emerging as an alternative classroom model that integrates active learning with advanced technology to improve learners' socialization and achievement. This research examines pre-service teachers' ( n  = 462) preferences toward this learning environment, as well as the predictive association between connectedness and other critical learning environment features. All pre-service teachers had at least one semester of actual experience as participants learning in this environment. The data was collected through a questionnaire, and a series of linear regressions were conducted to examine the hypothesized relationships. Connectedness was positive and significantly associated with all smart classroom features examined: inquiry learning, student negotiation, reflective thinking, functional design, multiple sources, usefulness, and ease of use. Pre-service teachers who preferred constructivist smart classroom learning environments tended to be those in their first year of post-secondary education, as well as those with higher levels of technology self-efficacy. Gender was not observed to significantly influence preferences. The findings show connectedness to be a central and critical feature that can be used to cultivate more appropriate environments from the participants' perspective.